2015
DOI: 10.1177/0269881115586284
|View full text |Cite
|
Sign up to set email alerts
|

Paliperidone palmitate in non-acute patients with schizophrenia previously unsuccessfully treated with risperidone long-acting therapy or frequently used conventional depot antipsychotics

Abstract: PALMFlexS, a prospective multicentre, open-label, 6-month, phase IIIb interventional study, explored tolerability, safety and treatment response in adults (n = 231) with non-acute but symptomatic schizophrenia switching to flexibly dosed paliperidone palmitate (PP) after unsuccessful treatment with risperidone long-acting injectable therapy (RLAT) or conventional depot antipsychotics (APs). Treatment response was measured by change in Positive and Negative Syndrome Scale (PANSS) total score from baseline (BL) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 34 publications
5
11
0
Order By: Relevance
“…The safety results in the present study suggest that the treatment for those patients receiving PP1M for 12 months or longer was well tolerated and ADRs were consistent with the known safety profile of PP1M. 13 , 18 , 24 , 25 This is noteworthy given that patients with newly diagnosed schizophrenia may be particularly susceptible to antipsychotic side effects, such as weight gain, metabolic abnormalities, and extrapyramidal symptom (EPS) side effects. 26 , 27 The mean changes in body weight and body mass index observed in the current study did not differ from those changes observed in other studies with PP1M in patients with more chronic schizophrenia.…”
Section: Discussionsupporting
confidence: 73%
“…The safety results in the present study suggest that the treatment for those patients receiving PP1M for 12 months or longer was well tolerated and ADRs were consistent with the known safety profile of PP1M. 13 , 18 , 24 , 25 This is noteworthy given that patients with newly diagnosed schizophrenia may be particularly susceptible to antipsychotic side effects, such as weight gain, metabolic abnormalities, and extrapyramidal symptom (EPS) side effects. 26 , 27 The mean changes in body weight and body mass index observed in the current study did not differ from those changes observed in other studies with PP1M in patients with more chronic schizophrenia.…”
Section: Discussionsupporting
confidence: 73%
“…PALMFlexS was a study analyzing the effectiveness of PP1M in patients diagnosed with clinically stable forms of SCZ spectrum disorders after unsuccessful treatment with RIS‐LAI or FGA‐LAI . The discontinuation rate in patients switched from RIS‐LAI or FGA‐LAI to PP1M ranged between 14.3% and 32.6% (main reasons for discontinuation being withdrawal of consent, onset of adverse events, or lack of efficacy).…”
Section: Resultsmentioning
confidence: 99%
“…47,[49][50][51]53,55 The only study reporting the advantage of PP1M on oral antipsychotics showed several limitations, the main being a suboptimal statistical power due to the small sample size and the inclusion in the study cohort of both new and old PP1M users. 54 The main causes of drug discontinuation before the planned study end were adverse events 45,46,61,62,65 and ineffectiveness. 47,51,59,62,65,66 The two available long-term studies on PPM3 showed a rate of premature discontinuation similar to that shown by the active comparator (PP1M).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations